The microsurgical infratentorial supracerebellar approach for lesions of the pineal gland: feasibility, morbidity, and functional outcomes from a single-center experience - Ahmed, Mamoun; Arend, Roman; Nordin, Niels; Scholz, Martin; Suchorska, Bogdana; Lucaciu, Robert; Jung, Suzin (Neurosurgical review, 2025)
Pineal gland lesions pose a significant surgical challenge due to the deep-seated nature of the pineal gland, as well as the limited field of view, and the complex vascular anatomy. The mainstay of surgical treatment, when necessary, is always histopathological clarity and gross total resection (GTR). We evaluate the surgical outcomes for pineal gland lesions, shedding light on functional outcomes, histological findings, and surgical complications. We analyzed patients with pineal gland lesions who underwent surgical treatment in our institution between September 2013 and May 2022. Patient demographics, clinical symptoms, surgical approaches, resection extent, surgery-related complications, and histopathological diagnosis were studied. Pre- and postoperative functional outcomes were assessed using the modified Rankin Scale (mRS) and were compared using the Student´s t-test. 32 patients (13 males, 19 females) were included. The mean age was 39 years old. We adopted the infratentorial supracerebellar approach (ITSC) in a semi-sitting position. 2 of these patients received preoperatively an endoscopic third ventriculocisternostomy (ETV) combined with endoscopic biopsy. The mean operating time for the ITSC approach was 170 min, whereas 53 min for the ETV with endoscopic biopsy. The mean length of stay was 13 days. The most common histopathological diagnosis was pineal cysts (38%). Surgical mortality was 0%, and morbidity was 28%. GTR was possible in 72% of patients treated using the ITSC approach. There was a functional outcome improvement, with a statistical significance measured via the Student´s t-test (p = 0.047). The ITSC approach remains safe and feasible when performed by an experienced surgical team, yielding a histopathological diagnosis and improvement of functional status.